Legal Measures for Crimes in the Field of Cryptocurrency Billing - BOKOVNYA, A.Y.; SHUTOVA, A.A.; ZHUKOVA, T.G.; RYABOVA, L.V. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Cryptocurrency crime cases continue to increase. The legal nature of cryptocurrency is analyzed, and it is concluded that nowadays, despite of some attempts to regulate cryptocurrency circulation legislatively, there are numerous gaps, most of which are in the field of criminal law. Based on the study of the available theoretical views of domestic, as well as the analysis of the judicial investigative practice materials of the legal sphere under consideration, the authors consider the necessity to carry out a work to formulate several areas that will streamline the criminal law relations in the field of cryptocurrency circulation.RESUMEN Los casos de criptomonedas continúan aumentando. Se analiza la naturaleza legal de la criptomoneda y se concluye que hoy en día, a pesar de algunos intentos de regular legislativamente la circulación de la criptomoneda, existen numerosas lagunas, la mayoría de las cuales están en el campo del derecho penal. Con base en el estudio de los puntos de vista teóricos disponibles de los nacionales, así como el análisis de los materiales de práctica de investigación judicial de la esfera legal en consideración, los autores consideran que es necesario llevar a cabo un trabajo para formular una serie de áreas que racionalizarán relaciones de derecho penal.